Dampak Penyakit Infeksi Parasit terhadap Status Gizi - Trasia, Reqgi First (Jurnal Ilmu Medis Indonesia, 2024)
guidelines, the authors conducted a systematic review to examine the effects of sanitation on major infectious diseases and nutrition in populations worldwide. Research methodology: This article reviews the extensive evidence on the impact of sanitation on important health outcomes, including diarrheal disease, STH infections, schistosomiasis, and nutritional status. Results: There was evidence of an association between sanitation and STH, but did not show no association was observed when the analysis was restricted to intervention studies only. This study found evidence consistent with previous reviews that sanitation is associated with lower odds of schistosomiasis, but the lack of intervention studies limits the quality of evidence and confidence in this association. Limitations: The nutritional findings in this study are similar to previous findings that reported no effect of sanitation on weight-for-age z-scores or weight-for-height z-scores. The results of the subset of studies reporting latrine coverage and latrine use suggest that, to observe comprehensive health benefits, sanitation coverage levels may need to be higher than those observed in this study. Contribution: This study provides evidence demonstrating the influence of sanitation on several key health outcomes, including diarrhea caused by A. lumbricoides, hookworms, S. stercoral, and schistosomiasis. The authors observed less clear evidence of the effects of sanitation on T. trichiurid and its nutritional value.